Tax Effects on sectors of the Colombian Economy - Flórez Bolaños, Jaime (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The aim of this article is to identify taxes effect (direct and indirect) on sectors of Colombia's economy. For this, it followed the line of work of Dietzenbacher & Romero (2007) which allows tracing the effects of one sector on another from calculation of the average propagation length (APL) which uses as input from the Input-Product Matrix (MIP-symmetric, product to product, basic prices, 2010). The main conclusion is a high asymmetry in the transmission of the tax effect among sectors.